2021
DOI: 10.1108/jdqs-07-2020-0016
|View full text |Cite
|
Sign up to set email alerts
|

Bitcoin and stock markets: a revisit of relationship

Abstract: The volatility of bitcoin (BTC) and time horizon is the center point for investment decisions. However, attention is not often drawn to the relationship between BTC and equity indices. Thus, the purpose of this paper is to investigate the volatility and time frequency domain of BTC with stock markets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…The results of this study are in line with research conducted by Sami & Abdallah (2020), Gil-Alana et al, (2020), and Hassanudin (2021 which states that cryptocurrency returns have a positive effect on stock price indices.…”
Section: The Effect Of Cryptocurrency Return (X1) On the Stock Price ...supporting
confidence: 91%
See 1 more Smart Citation
“…The results of this study are in line with research conducted by Sami & Abdallah (2020), Gil-Alana et al, (2020), and Hassanudin (2021 which states that cryptocurrency returns have a positive effect on stock price indices.…”
Section: The Effect Of Cryptocurrency Return (X1) On the Stock Price ...supporting
confidence: 91%
“…In addition, the positive influence of cryptocurrency returns is also caused by cryptocurrency can be used as an investment option to diversify portfolios due to the low correlation and even a negative correlation between cryptocurrency and stock prices. This portfolio diversification theory is supported by the results of research by Gil-Alana et al, (2020) and Hassanudin (2021), which state that there is a negative correlation between cryptocurrencies and stock prices, so that there is a significant role of cryptocurrencies in investors' portfolios because it serves as a diversification option that confirms that cryptocurrencies are a new investment asset class, investors see Cryptocurrencies as a complement to their portfolio are not a substitute.…”
Section: The Effect Of Cryptocurrency Return (X1) On the Stock Price ...mentioning
confidence: 83%
“…That is because capital markets rely heavily on shocks in Bitcoin based on their correlation to stock returns (Hung, 2021). , Thaker & Mand (2021) and confirmed that the explosive movement of Bitcoin has caused instability in the capital market. Even the impact of Bitcoin is more vital than macroeconomic conditions (Ahmed, 2021;Salisu et al, 2019), so Bitcoin becomes a magnet for everyone (Gil-Alana et al, 2020).…”
Section: Sourcementioning
confidence: 82%
“…Besides, the global Islamic capital market also showed an increase in total returns of up to 32.6% in 2019, as well as a year-on-year increase in the global shariah index of 13.6% between the period 2015 -2020 (Ahmad et al, 2021;Islamic Financial Services Board, 2020), in addition, there are 1.6 billion Muslim populations or 23% of the world's population, contributing to the growth of Islamic Stock Exchange Markets (G. Tuna, 2019; V. E. Tuna et al, 2021). However, the existence of Islamic capital markets is threatened by Bitcoin, which has developed as a store of value and commodity assets (Baur et al, 2017;Paule-Vianez et al, 2020;Selgin, 2015;Sotiropoulou & Guégan, 2017), so there is a substantial interest to allocate investments in Bitcoin (Baur et al, 2017;Thaker & Mand, 2021), Even global investment giants such as MicroStrategy, Grayscale Investment, Morgan Stanley Wealth Management, VanEck Global Investment Manager to the State of El Salvador have changed their investment portfolios to Bitcoin (Bonello, 2020;EFG Asset Management, 2021;Galindo & Shalett, 2021;VanEck, 2021), so bitcoin's influence on the capital market has grown stronger in recent years (Giudici & Abu-Hashish, 2019;Goodell & Goutte, 2021;Kurka, 2019;Matkovskyy & Jalan, 2019;Salisu et al, 2019). However, most of the Global muslim community has rejected Bitcoin regarding halal or haram issues, fraud, speculative, terrorism funding to incompatible with Islamic financial principles (Abubakar et al, 2019;Baur et al, 2017;Meera, 2018;Polas et al, 2020;Teichmann, 2018;Whyte, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Hodoshima and Otsuki compared the performance of Bitcoin and stocks based on the Sharpe ratio and found that the Sharpe ratio of some stock assets is superior to Bitcoin [8]. Hassanudin et al looked at the relationship between Bitcoin and stock indices as well as investigated the volatility and time-frequency domain of BTC and the stock market [9]. Since the research on the establishment of investment portfolios of different types of assets is not perfect, this article used the historical data of stocks, goods and cryptocurrencies, established some investment portfolios and predicted the rate of return.…”
Section: Introductionmentioning
confidence: 99%